Effects of psychological variables on the relationship between customer participation behavior and repurchase intention: Customer tolerance and relationship commitment - Soo-Jeong Kim; Byung-Hwan Hyun (Economies, 2022)
The inseparability of the production and consumption of services without quality control makes it difficult to fully meet the diverse needs of customers. Despite a company's continuous efforts to satisfy customers with perceived quality aimed at service success, if the customers' expectations are not met, the customers will not be satisfied. This study empirically analyzed the effects of customer tolerance and relationship commitment as psychological variables on the relationship between customer participation and repurchase intentions. According to the results of the analysis, relationship benefits, which are a motivation factor for customer participation, had significant effects on customer participation. In addition, customer participation showed significant effects on customer tolerance and relationship commitment. Furthermore, both customer participation and tolerance had significant effects on repurchase intentions; however, relationship commitment was found to have no significant effect on repurchase intentions. The results of this study indicate that customer tolerance formed through customer participation behavior improves customers' satisfaction with perceived service quality thanks to the shared sense of responsibility that makes customers tolerate a failure of the final service after the service encounter process, thereby increasing repurchase intentions, which prevents the consumptive expenses invested into to recovering services after the company's service failure. As such, the results of this study provide meaningful implications for sustainable management.
Keywords: 330; customer participation; customer tolerance; relationship benefits; relationship commitment; repurchase intention